CONTRIBUTION OF NGOS IN PROMOTING SPORTS - Agarwal, Mukesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
NGOs play an important role in increasing the scope of sports. They are actively involved in raising awareness about sports, building playgrounds, making arrangements for implementation of sports, training players, and organizing various arrangements to promote sports. NGOs work in collaboration with the government and other institutions in promoting sports, which means sports. Non-Government Organization, in Hindi we call it NGO. Well, it is a non-governmental organization but it works for the public in collaboration with the government. With the help of NGOs, all government schemes reach our doorstep. With the help of NGOs, the government does development work. These NGOs also work as an implementation agency.